(untitled) (Jurnal Hortikultura Indonesia, 2021)
Abiu (Pouteria caimito) is an exotic tropical plant that has many benefits for health. Abiu is an interesting plant because of its various bioactive compounds, therefore it is necessary to conduct research on various bioactive compounds that are contained in each part of abiu plant. The purpose of this study was to identify and evaluate the bioactive compounds of the extract of different parts of abiu and their benefits. The study used 5 (five) parts of abiu plant, i.e. shoot leaves, mature leaves, unripe fruit, ripe fruit pulp, and ripe fruit peel. The experiment was conducted in a completely randomized design (RCD) with five replicates. The contents of bioactive compounds were determined using gas chromatography mass spectrometry (GCMS). The results showed that all parts of the abiu plant contained bioactive compounds that have benefits for health, especially as anti-cancer. These compounds are 1-(2-Hydroxyethyl)-1,2,4-triazole, 5-hydroxy methyl furfural, 1-methyl-5-fluorouracil and trans-geranylgeraniol. Compound of 1-(2-hydroxyethyl) -1,2,4-triazole was found on contained in shoot leaves and mature leaves of abiu. Compound of 5-hydroxy methyl furfural was contained in unripe fruit, ripe fruit pulp and ripe fruit peel of abiu. Compound of 1-methyl-5-fluorouracil was found on ripe fruit pulp of abiu. Compound of trans-geranylgeraniol was found on ripe fruit pulp and ripe fruit peel of abiu. Keywords: Anti-cancer, antioxidant, extracts, GCMS, health.